Overweight and Obesity with Lifestyle and Dietary Habits among Students: Kelebihan Berat Badan dan Obesitas pada Siswa Berkaitan dengan Gaya Hidup dan Kebiasaan Makan - Idan, Jamal Sabr; Jawad , Ahmed Salam; Kadhim , Sajad Ahmed (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Overweight and obesity are increasing global health challenges, closely linked to cardiovascular diseases, insulin resistance, and other metabolic disorders. Specific Background: University students in developing countries are particularly vulnerable due to poor dietary habits, sedentary lifestyles, and limited health awareness. Knowledge Gap: Despite growing concern, limited evidence exists on the combined influence of dietary and lifestyle factors on obesity among Iraqi students. Aim: This study aimed to examine the association between body mass index (BMI), dietary habits, and lifestyle behaviors among students at the Babylon Technical Institute. Results: A cross-sectional survey of 202 students revealed that while most participants had a normal BMI, a notable proportion were overweight or obese, with females at higher risk of central obesity. Although 54% reported eating three meals daily, dietary patterns were generally neutral or unhealthy, characterized by sugary drink consumption and meal skipping. Lifestyle factors showed a statistically significant association with nutritional status (p = 0.05), whereas dietary habits did not. Novelty: This is among the first studies in Iraq to simultaneously assess dietary and lifestyle factors in relation to BMI among technical institute students. Implications: The findings highlight the urgent need for institutional interventions, including awareness campaigns, healthier campus food environments, and promotion of physical activity to prevent long-term health risks.Highlight : Many students had normal weight, but a significant number were overweight or obese. Dietary habits were mostly unhealthy or neutral, with high intake of sugary drinks. Lifestyle showed a significant association with nutritional status. Keywords : BMI, Obesity, Lifestyle, Dietary Habits, Students